Soul and Musical Theater: A Comparison of Two Vocal Styles - Hallqvist, Hanna (2017)
The phonatory and resonatory characteristics of nonclassical styles of singing have been rarely analyzed in voice research. Six professional singers volunteered to sing excerpts from two songs pertaining to the musical theater and to the soul styles of singing. Voice source parameters and formant frequencies were analyzed by inverse filtering tones, sung at the same fundamental frequencies in both excerpts. As compared with musical theater, the soul style was characterized by significantly higher subglottal pressure and maximum flow declination rate. Yet sound pressure level was lower, suggesting higher glottal resistance. The differences would be the effects of firmer glottal adduction and a greater frequency separation between the first formant and its closest spectrum partial in soul than in musical theater.